Direct current field induced asymmetrical DC-resistivity degradation in SrTiO3-based grain boundary layer ceramic. Issue 10 (July 2019) - He, Fan; Lv, Ming; Lu, Minghui; Cao, Lin; Wang, Qingran; Li, Ruqiang; Ding, Mingjian
Abstract: Degradation of SrTiO3-based grain boundary barrier layer ceramic was studied by applying a direct current voltage of 40 V for 12 days at room temperature. The degradation of the ceramic mainly showed as an asymmetrical resistivity degradation with the degradation of the reverse resistivity being greater than the forward resistivity. By using a scanning microwave impedance microscopy (SMIM), we observed an asymmetry in carrier concentration within the grain boundaries after the aging treatment. It was proposed that the asymmetrical migration of oxygen ions in O-rich region caused the asymmetrical degradation of resistivity. Direct current induced degradation reduces the effectiveness of ceramics capacitors and great efforts should be made to prevent this type of degradation.